The not very patrilocal European Neolithic : strontium, aDNA, and archaeological kinship analyses - Ensor, Bradley E., 1966- (Archaeopress Archaeology, 2021)
Two decades of strontium isotope research on Neolithic European burials - reinforced by high-profile ancient DNA studies - has led to widespread interpretations that these were patrilocal societies, implying significant residential mobility for women. This volume questions that narrative from a social anthropological perspective on kinship.